Utilization of strategies for ensuring effective security of data in government parastatals in Abia state - Faith Chukwudi Nwaukwa; Anioke; Peggy Onyefuruchi (Journal of Management and Science, 2023)
The need to protect data of government parastatals from unauthorized access and breaches necessitated this study. The study ascertained the utilization of strategies for ensuring the security of data in government parastatals in Abia State. One research question and one null hypothesis guided the study. The study adopted survey research design, with a population of 351 data managers in government parastatals studied without sampling. A-14 item structured questionnaire was used to collect data for the study. The face and content validity of the instrument was determined using four experts while the reliability was established using pilot-test and data obtained calculated using Cronbach Alpha formula which yielded correlation coefficient of .87. Descriptive mean and standard deviation were used to answer the research question while ANOVA was used to test the null hypothesis at .05 significant level. Findings revealed that office employees in government parastatals in Abia State utilize network control strategy to a low extent in ensuring security of data. Years of working experience of data managers did not significantly influence their mean responses in this regard. Hence, the researchers concluded that more training/re-training of office staff is needed on how to utilize network control strategy to ensure effective security of data in government parastatals in Abia State. It was recommended among others that; management of government parastatals in Abia State should organize regular data security training workshops for all their office staff to enable them up-data their skills and competencies in utilizing network control strategy for security of organizations’ data.